SOBRE LAS PRIMERAS TRADUCCIONES ESPAÑOLAS DE LOS CONTES DROLATIQUES DE BALZAC - Lafarga, Francisco (Anales de Filología Francesa, 2006)
On the first Spanish translations of the Contes drolatiques by Balzac Description and analysis of the first Spanish versions of the Contes drolatiques, dating from the end of the 19th. century - early 20 th. century. The paratexts from differente editions will be considered, along with certain interesting textual elements, whih will enable us to stablish a contrastive study of the translations.